2023
DOI: 10.3390/cancers15072071
|View full text |Cite
|
Sign up to set email alerts
|

High-Multiplex Aptamer-Based Serum Proteomics to Identify Candidate Serum Biomarkers of Oral Squamous Cell Carcinoma

Abstract: Improved serological biomarkers are needed for the early detection, risk stratification and treatment surveillance of patients with oral squamous cell carcinoma (OSCC). We performed an exploratory study using advanced, highly specific, DNA-aptamer-based serum proteomics (SOMAscan, 1305-plex) to identify distinct proteomic changes in patients with OSCC pre- vs. post-resection and compared to healthy controls. A total of 63 significantly differentially expressed serum proteins (each p < 0.05) were found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Using proximity ligation or DNA-based aptamers to capture protein targets of interest, respectively, both assays can measure thousands of proteins of varying abundance from a small biofluid sample. Recent studies have demonstrated the ability of these techniques to uncover cancer-related proteomic signals 220 222 . Compared to ctDNA, liquid biopsy proteomics and transcriptomics are early in their development, but recent advances suggest that these analytes may also play a more prominent role in the field in the future.…”
Section: Current Perspective Of Blood-based Biomarkersmentioning
confidence: 99%
“…Using proximity ligation or DNA-based aptamers to capture protein targets of interest, respectively, both assays can measure thousands of proteins of varying abundance from a small biofluid sample. Recent studies have demonstrated the ability of these techniques to uncover cancer-related proteomic signals 220 222 . Compared to ctDNA, liquid biopsy proteomics and transcriptomics are early in their development, but recent advances suggest that these analytes may also play a more prominent role in the field in the future.…”
Section: Current Perspective Of Blood-based Biomarkersmentioning
confidence: 99%